Implementation And Supervision Of Stakeholders-Based Education Marketing East Java Indonesia - Eko Sigit Purwanto; Akhyak; Achmad Patoni; Imam Junaris (International Journal of Science, Technology & Management, 2021)
Private schools must try to improve education marketing management in order to get more students that will later support learning activities in schools. Marketing management in this research is how to introduce educational products, invite and influence people to become consumers or service users in an educational institution. This study uses a qualitative approach that has a post positivistic or interpretive paradigm with the aim of understanding the phenomena that occur in the field. This type of research is multisite. The data collection in this study was carried out by means of participant observation, in-depth interviews and documentation. Furthermore, the researchers analyzed the data using two methods, i.e.: on-site data analysis and cross-site analysis using the Miles Huberman interactive model, known as reduction and presentation of data and drawing conclusions. The results of this study are: 1) implementation of stakeholder-based educational marketing management which is carried out by carrying out the placement tests, fulfilling qualifications and improving teacher professionalism, fulfilling facilities and infrastructure, providing opportunities for students to take extra-curricular activities, targeting output (students) who are in good attitudes, smart, healthy, accomplished, and competitive, conducts routine evaluations, assimilates with stakeholders, and achieves customer satisfaction. The optimistic attitude and deep love of the alumni can then be called market fanatics, coming out from market ideology, 2) integrated supervision by combining inherent supervision and follow-up plans. Both institutions strive to guard all plans to achieve perfect targets in terms of educational marketing by eliminating errors or zero defects.